Proton pump inhibitor-related headaches: A nationwide population-based case-crossover study in Taiwan. (March 2015) - Liang, Jen-Feng; Chen, Yung-Tai; Fuh, Jong-Ling; Li, Szu-Yuan; Chen, Tzeng-Ji; Tang, Chao-Hsiun; Wang, Shuu-Jiun
Background: Headaches resulting from proton pump inhibitor (PPI) use could cause discontinuation of PPI in as many as 40% of patients who experience such headaches. Previous studies focusing on acute headache risk from PPI use are rare and limited to clinical trials of a single PPI. Objectives: To investigate the association between PPI use and headache with a nationwide population-based case-crossover study. Methods: Records containing the first diagnosis of any headache, including migraine and tension-type headaches, were retrieved from Taiwan National Health Insurance Database (1998–2010). We compared the rates of PPI use for cases and controls during time windows of 7, 14, and 28 days. The adjusted self-matched odds ratios (ORs) and 95% confidence intervals (CIs) from a conditional logistic regression model were used to determine the association between PPI use and headache. Results: Overall, 314, 210 patients with an initial diagnosis of any headache during the study period were enrolled. The adjusted ORs for headache risk after PPI exposure were calculated for three time periods (within 7 days = 1.41, p = 0.002, 95% CI 1.14–1.74; within 14 days = 1.36, p < 0.001, 95% CI 1.16–1.59; within 28 days = 1.20, p = 0.002, 95% CI 1.07–1.35). Subgroup analyses showed female patients had an increased risk of headache. Among PPIs, lansoprazole and esomeprazole had the highest risks of headache incidence, which were similar to that of nitrates. Conclusion: PPI usage is associated with an increased risk for acute headache. Female patients and use of lansoprazole or esomeprazole present the greatest risks of headache.